Changes in Pain Sensitization After Bariatric Surgery. Issue 10 (27th September 2018) - Stefanik, Joshua J.; Felson, David T.; Apovian, Caroline M.; Niu, Jingbo; Margaret Clancy, M.; LaValley, Michael P.; Neogi, Tuhina
Abstract : Objective: To evaluate changes in pain (at the knee and elsewhere) and pain sensitization in obese subjects with knee pain who were having bariatric surgery compared with similarly obese individuals who were undergoing medical management. Methods: This study included a cohort of subjects who were having bariatric surgery and those undergoing medical management. Knee pain severity of the more painful knee (index knee) was assessed at baseline and at 12 months using the Western Ontario and McMaster Universities Osteoarthritis Index. The pressure pain threshold (PPT) was evaluated at the index patella and the right wrist. Low patella PPT may reflect peripheral and/or central sensitization, and low wrist PPT may reflect central sensitization. The mean change in measures of pain and pain sensitization was analyzed in the surgery and medical management groups separately. Results: A total of 45 subjects in the surgery group and 22 in the medical management group completed baseline and follow‐up visits. The mean weight loss was 32.7 kg (29.0%) and 4.6 kg (4.1%) in the surgery and medical management groups, respectively. Knee pain decreased only in the surgery group, in which the PPT at the patella improved by 38.5% ( P = 0.0007) and at the wrist by 30.9% ( P = 0.005). There was no significant change in PPT in the medical management group. Conclusion: Persons who underwent bariatric surgery experienced an improvement in pain sensitization, reflected by improvements in PPT. This improvement was observed not only at the patella, but also at the wrist, suggesting that central sensitization improved after bariatric surgery.